John within Judaism religion, ethnicity, and the shaping of Jesus-oriented Jewishness in the fourth gospel - Cirafesi, Wally V. (Boston BRILL, 2021)
Intro -- Contents -- Acknowledgements -- Abbreviations -- Chapter 1 Introduction: John and Judaism, Then and Now -- 1 The Questions, the Problems, and the Argument -- 2 Scholarly Conceptions of "John and Judaism" -- 2.1 The "Johannine Community" and the "Parting of the Ways" -- 2.2 Replacement, Supersessionism, and Expropriation in Johannine "Anti-Judaism" -- 2.3 John and the Concept of "Religion" -- 3 Some Prolegomena to the Study of John and Judaism -- 4 The Contribution of This Study -- Chapter 2 John and the Problem of Ancient "Judaism" -- 1 Introduction -- 2 "Judaism" in Antiquity: Religion and Ethnicity, Unity and Diversity -- 2.1 "Religion" or "Ethnicity"? -- 2.2 Unity and Diversity in Ancient "Judaism" -- 2.3 Modeling Diversity: "Priestly-Oriented" and "Diasporic" Modes of Identity -- 3 The Meaning Potential of Ioudaios in Antiquity: MethodologicalObservations -- 4 Conclusion -- Chapter 3 The Jewish People and the Children of Israel's Godin John -- 1 Introduction -- 2 Ethnos and "Peoplehood" in Greco-Roman and Jewish Antiquity: Between Genealogy and Way of Life -- 3 The Ioudaioi, Jewishness as Genealogy, and the Birth of God's Children in John's Gospel -- 3.1 Jewishness as Genealogy and the Boundaries of God's People in John 7:1-10:21 -- 3.1.1 John 7:14-24, 35: Eighth-Day Circumcision and a Mission to (Judaizing) Gentiles -- 3.1.2 John 8:30-59: Slaves, Mamzerim, and Doing as Abraham Did -- 3.1.3 John 9:1-41: Sinners, "Godfearers," and Doing the Will of the Jewish God -- 3.1.4 John 10:16: One Flock, One Shepherd, Different Sheep -- 3.1.5 Conclusions on John's Use of Ioudaioi -- 3.2 The Birth of God's Children and Their Relationship to the "World" -- 4 Conclusion -- Chapter 4 "We Have a Law …" (John 19:7) The Ancestral Law and Its Laws in John -- 1 Introduction: Ethnos and Law in Greco-Roman and Jewish Antiquity.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books; Hochschulschrift